Freedom Movement in Undivided Dharwad District: Role of Adiveppa Hasabi and Rajashekarappa Hoskeri - Pulakeshi B. Kamannavar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The question that often arises is: what exactly constitutes the freedom movement? What is the contribution of freedom fighters to the nation and the people? Among them, what was the role of women freedom fighters, and how did classical Kannada culture encourage people to participate in the movement? This article focuses on a detailed study of the freedom struggle in the undivided Dharwad district of Karnataka, highlighting the contributions of prominent leaders such as Adiveppa Hasabi and Rajashekarappa Hoskeri during the Quit India Movement of 1942. The study examines the differences in terms of place, person, and time among the participants of the freedom struggle, offering a local perspective on the national movement.
Keywords: Quit India Movement; Commemoration; Boycott; Countrymen; Triggered